Philanthropy, Scholarships and Student navigations in a changing South African educational landscape - Day, Helen (School of Education, 2024)
This dissertation explores the intersection of public education, philanthropy, and private sector funding in South Africa, and the different ways that students that receive scholarships via private funding navigate their respective educational spaces. The discussion focuses on how debates on scholarships, provided by philanthropic organisations, play out against the larger landscape of public-private educational partnerships in South Africa, and links that to the changing form of philanthropy in South Africa over time. In doing so, the dissertation introduces the voices and stories of 22 scholarship recipients scattered across the South African educational and geographical landscape (born and raised in 7 different provinces). This offers opportunities to tease out the different connections between philanthropic contributions and public education, and to question the growing influence of public-private partnerships and their stakeholders on the ways that public education and its role is conceptualised in South Africa. The goal of the dissertation is to highlight some implications that philanthropic scholarships provide for marginalised students within public institutions in South Africa, and the implications that they may have for the public education system in a context where global and local private interests have a firm agenda vis-a-vis the reconfiguration of overall public education systems. By engaging with the lived experiences and stories of 22 students receiving scholarships, the dissertation casts a spotlight on some of the opportunities, contradictions, struggles, and constraints that students within philanthropic public-private partnership spaces in South Africa often confront. The dissertation utilises the 3R framework (redistribution, representation, recognition) of Nancy Fraser, to consider some of the nuances, conflicts, and challenges that private philanthropy seems to bring to current debates about public schooling. The goal of using these is to tease out how emerging new pathways and approaches within the public-private educational domain may change how education provision for students in challenging and marginalised contexts is reconceptualised over the 21st century.